Leveraging International Health Regulations (2005) to enhance health security in the Eastern Mediterranean Region: a retrospective analysis from 2016 to 2023 - Dalia Samhouri; Mohamed Elhakim; Amgad Elkholy; Mahgoub Hamid (BMJ Public Health)
Introduction The WHO Eastern Mediterranean Region (EMR), consisting of 22 member states, faces significant health security challenges exacerbated by socioeconomic, political and environmental factors. This study aims to assess the efforts to enhance health security in the EMR from 2016 to 2023 through the implementation of the International Health Regulations (IHR) (2005) core capacities.Methods A narrative review was conducted using IHR Monitoring and Evaluation Framework (MEF) tools, such as the State Party Self-Assessment Annual Report (SPAR) and the Joint External Evaluation (JEE), to evaluate the region’s preparedness and response capabilities. Other assessments, such as the Universal Health and Preparedness Review (UHPR), after-action and intra-action reviews and simulation exercises, were included.Results The evaluations identified critical gaps in health security infrastructure, highlighting the need for comprehensive strategies and external support, including the Pandemic Fund and National Action Plans for Health Security. While progress has been made, challenges remain due to emerging and re-emerging diseases and regional humanitarian crises.Conclusion Despite improvements, the EMR continues to face significant health security challenges. Increased advocacy, capacity building and multisectoral collaboration, particularly through the One Health approach, are essential for future preparedness.